Morning and nocturnal serum melatonin rhythm levels in patients with major depressive disorder: an analytical cross-sectional study - Khaleghipour, Shahnaz (2012)
CONTEXT AND OBJECTIVE: The pineal gland is an adaptive organ that precisely regulates the biological rhythms of melatonin brain hemostasis. Variation in the regulation of melatonin rhythms is a likely cause of depressive disorder. The purpose of this study was to measure serum melatonin levels in patients with major depressive disorder (MDD) and normal control subjects. DESIGN AND SETTING: Analytical cross-sectional study at the industrial medical unit of the Iron Smelting Company of Isfahan, Iran. METHODS: The morning and nocturnal serum melatonin levels of patients and controls were measured using the enzyme-linked immunosorbent assay (ELISA) method. All data were assessed using variance analysis. RESULTS: The morning and nocturnal serum melatonin levels of depressed and healthy subjects differed (P ≤ 0.05). The nocturnal serum melatonin levels of depressed women were lower than those of depressed men (P ≤ 0.05). CONCLUSIONS: The findings of this study showed that the nocturnal serum melatonin levels in the depressed patients were lower than in the controls. Thus, the peak melatonin phase in the depressed patients was reached with delay. CLINICAL TRIAL REGISTRATION NUMBER: NCT01357083